NUMB and Syncytiotrophoblast Development and Function: Investigation Using BeWo Choriocarcinoma Cells - Carey, Julie (Université d'Ottawa / University of Ottawa, 2012)
The role of NUMB, a protein important for cellular differentiation and endocytosis in non-placental cells, was investigated in syncytiotrophoblast development and function in the human placenta. The BeWo choriocarcinoma cell line was used as a model for villous cytotrophoblast cells and syncytiotrophoblast to investigate NUMB’s involvement in differentiation and epidermal growth factor receptor (EGFR) endocytosis. NUMB isoforms 1 and 3 were found to be the predominant isoforms and were upregulated following forskolin-induced differentiation. Overexpression of NUMB isoforms 1 and 3 did not mediate differentiation or EGFR signaling. Immunofluorescence analysis revealed that NUMB colocalized with EGFR at perinuclear late endosomes and lysosomes following EGF stimulation. We have demonstrated for the first time that NUMB isoforms 1 and 3 are expressed in BeWo cells, are upregulated in forskolin-differentiated BeWo cells and are involved in ligand-dependent EGFR endocytosis in BeWo cells.
Keywords: NUMB; BeWo; EGFR; placenta; endocytosis